Personalizing Politics and Realizing Democracy - Caprara, Gian Vittorio and Vecchione, Michele (New York Oxford University Press, 2017)
Personalizing Politics and Realizing Democracy brings to light recent and important contributions on personality psychology with respect to the democratic process.
Include References and Index
Keywords: Political participation--Psychological aspects -- Political psychology -- Democracy--Psychological aspects